HUBUNGAN ANTARA TINGKAT ANSIETAS DENGAN SIKLUS MENSTRUASI PADA WUS DI LEMBAGA PERMASYARAKATAN KOTA PADANGSIDIMPUAN - nasution, izmi fadhilah (Jurnal Kesehatan Ilmiah Aufa Royhan, 2023)
ABSTRACT Background: The menstrual cycle is the time from the first day of menstruation until the next menstrual period arrives, with a normal range of 21-35 days. One of the factors that influences the menstrual cycle is anxiety. Objective: To determine the relationship between anxiety levels and the menstrual cycle in WUS in community institutions in Padangsidimpuan City. Method: This research uses descriptive analytics with a cross sectional approach. The population in this study were all female prisoners of reproductive age. Statistical analysis using Chi-Square. This research began in November 2023 until December 2023. Results: The results of the univariate analysis showed that the level of society experienced mild anxiety by 4 respondents (25%), who experienced moderate anxiety as many as 8 respondents (50%) and experienced severe anxiety as many as 4 respondents (25%). The chi-square test results show p-value= 0.032. Conclusion: It can be concluded that there is a significant relationship between the level of anxiety and menstrual cycle disorders in WUS in community institutions in Padangsidimpuan City.